2022
DOI: 10.21203/rs.3.rs-2245130/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of IRNSS-retrieved integrated precipitable water over a few locations in India

Abstract: We estimated integrated precipitable water (IPWV) over a few locations in India, namely Bhubaneswar, Gadanki, Goa, Kanakapura, and Kolkata, from the tropospheric slant delay (TSD) obtained from the Indian Regional Navigation Satellite System (IRNSS). We attempted to find the factors that control the IPWV. We show that the total solar irradiance (TSI) controls IPWV beyond doubt. The latter is best explained as a function of surface temperature (ST), surface pressure (SP), relative humidity (RH), and TSI. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…At that time, in India, few service centres are available for electric vehicles. So, manufacturers have to establish EV service centres that can quickly solve the issues and queries of the customers (Singal, 2021). Many incidents have recently shown that electric vehicles have caught fire for technical reasons.…”
Section: Strengthen Manufacturing Systemmentioning
confidence: 99%
“…At that time, in India, few service centres are available for electric vehicles. So, manufacturers have to establish EV service centres that can quickly solve the issues and queries of the customers (Singal, 2021). Many incidents have recently shown that electric vehicles have caught fire for technical reasons.…”
Section: Strengthen Manufacturing Systemmentioning
confidence: 99%
“…Work motivation energizes, pushes, and inspires employees, which is an element for a self-motivated and successful workplace. Motivation increases efficiency and innovativeness in the workplace, increases job satisfaction and job security, and helps the company to sustain in challenging situations (Jaiswal, 2022). Generating high level employee motivation in production will increase the number of products produced, reduces the occurrence of quality control issues and minimizes downtime that results to employees retain in the company in a long-term span and helps the company to reduce costs associated with training new and recruiting employees (Starkey, 2022).…”
Section: Introductionmentioning
confidence: 99%